The malignant dialogue between cancer-associated fibroblasts and osteosarcoma cells: microenvironment-mediated drug resistance and therapeutic targets - Xiufeng Wang; Cong Luo; Danying Zhang (Frontiers in Immunology)
Cancer-associated fibroblasts (CAFs) are pivotal in shaping the immunosuppressive and chemoresistant tumor microenvironment (TME) of osteosarcoma (OS). This review explores how CAFs drive OS progression through paracrine signaling (e.g., TGF-β, IL-6), extracellular matrix (ECM) remodeling, exosome-mediated crosstalk, and metabolic reprogramming. We highlight CAF heterogeneity (e.g., myCAFs, iCAFs) and their roles in therapy resistance, emphasizing emerging strategies such as FAP inhibitors, TGF-β blockers, and CXCR4 antagonists. Combining these approaches with immunotherapy or chemotherapy offers promise for overcoming chemoresistance. Challenges like CAF plasticity and biomarker development are discussed, alongside future directions for precision targeting in OS.